Detection of invasive aspergillosis in bone marrow transplant recipients using real-time PCR - Mojtaba Nabili; Tahereh Shokohi; Ghasem Janbabaie; Mohammad Bagher Hashemi-Soteh; Kamran Ali-Moghaddam; Seyed Reza Aghili (Journal of Global Infectious Diseases, 2013)
Objective: The invasive aspergillosis (IA) is a serious opportunistic infection caused by various species of Aspergillus in immunocompromised individuals. Basically, rapid and early diagnosis prevents IA progression. In this study we performed a Real Time PCR/ Fluorescence Resonance Energy Transfer (FRET) for diagnosis of IA in hematologic malignancies and bone marrow transplant recipients. Materials and Methods: Sixty two patients with hematologic malignancies and marrow transplant recipients were evaluated for IA in Sari and Tehran from 2009 to 2010. The primer and hybridization probe were designed to amplify the specific sequence of 18S rRNA genes using Light Cycler system and FRET. Galactomannan (GM) assay was performed on serums which obtained from selected patients using the Platelia Aspergillus kit. Results: According to the criteria defined by the European Organization for Research and Treatment of Cancer and Mycoses Study Group (EORTC/MSG) for IA, 18 (29%) patients out of 62 patients were stratified into probable and possible groups. The female-to-male ratio was 1:2; the mean age of the patients was 36 years. The most common malignancies in these patients were acute lymphoblastic leukemia (38.9%). The minimum detection limit was 10 conidia (10 1 CFU/ml) equivalents (100 fg) per PCR reaction. GM assay was positive in 20.9% and real-time PCR probe set assay were positive in 17.7% patients who had clinical signs and host factor according to the mentioned criteria. Conclusion: Using the Real-Time PCR/FRET assay in whole blood specimens seems to be a promising method for diagnosis of IA, especially when used in combination with the GM detection test.